If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + (-5) = -17 m + -5 = -17 Reorder the terms: -5 + m = -17 Solving -5 + m = -17 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + m = -17 + 5 Combine like terms: -5 + 5 = 0 0 + m = -17 + 5 m = -17 + 5 Combine like terms: -17 + 5 = -12 m = -12 Simplifying m = -12
| .15x-3=.4(x-5) | | 6/7=3x | | 2x-(xb+ab)+2ab=0 | | 1/5=80/g | | x-5/2-3=x-2/3 | | 4e-19=-3(3-4) | | 96=y+5y | | 4/3(2x-1)=12 | | -7(3y+9)=-15 | | 5+(2a/-3)=5/11 | | -4x^2+9x+7= | | (2x+11)/3=15 | | 6x-1=-2x+31 | | m/292=7/25 | | 1000(8x-10)=50(589+100x) | | 1-3/4=n | | 2x-xb+ab=0 | | m-4n=8form | | 3c/7=-2/3 | | 9a^12= | | 20k+90=10k+100 | | 9/36=x/480 | | 1/3x-2/7=4 | | 6x=3x-2(x-5) | | 5x-2(x-5)=10 | | 5(-1/25)-3x=4(-1/25)+6x-1 | | 1/5n+1/6n=1/22 | | 9y+(4y+3)= | | -9-x=7x+87 | | 5x-19=46 | | 13/5=72/z | | 3/1.5 |